The "Put Your Heel Down" campaign. - Ng, Melissa Yun Suan. (2011)
This paper presents the “Put Your Heel Down” campaign, a youth-led initiative by three final year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. The public communication campaign aims to promote awareness of sexually transmitted infections (STIs) among female youths aged 18 to 25. It also looks to empower these females to make the right sexual health decisions, through a series of fun and educational activities. The key strategies that were put in place are documented in this comprehensive report. These measures helped to create a successful campaign which was able to effectively meet its various objectives. This paper provides conclusive research that helped to mould the direction of the communication plans, strategies, execution, as well as an evaluation of the campaign. The sustainability of the campaign will be highlighted, and the report will be concluded with recommendations on how the campaign can be further developed.